A Typical Metal‐Ion‐Responsive Color‐Tunable Emitting Insulated π‐Conjugated Polymer Film. Issue 43 (7th July 2016) - Hosomi, Takuro; Masai, Hiroshi; Fujihara, Tetsuaki; Tsuji, Yasushi; Terao, Jun
Abstract: We report the synthesis of an insulated π‐conjugated polymer containing 2, 2′‐bipyridine moieties as metal coordination sites. Metal coordination to the polymer enabled easy and reversible tuning of the luminescent color without changes to the main chain skeleton. The permethylated α‐cyclodextrin (PM α‐CD)‐based insulation structure allowed the metalated polymers to demonstrate efficient emission even in the solid state, with identical spectral shapes to the dilute solutions. In addition, the coordination ability of the metal‐free polymer was maintained in the solid state, resulting in reversible changes in the luminescent color in response to the metal ions. The synthesized polymer is expected to be suitable for application in recyclable luminescent sensors to distinguish different metal ions. Abstract : Metal‐ion sensor : An insulated π‐conjugated polymer containing metal‐binding sites was synthesized. The coordination of metal ions to these sites alters the electronic properties of the polymer considerably. As a consequence the emission wavelength of the polymer varies and the polymer acts as a sensor for metal ions.